Two new Veraphis species in China (Coleoptera, Staphylinidae, Scydmaeninae) - Jałoszyński, Paweł (Zootaxa, 2024)
Two new species of Veraphis Casey are described, based on specimens collected in China: V. shaanxiana sp. nov., and V. dabashana sp. nov. These discoveries increase the number of Chinese Veraphis species to eight. A distribution of Veraphis in China and comparison of aedeagi of all species are given to facilitate identifications.